Pengaruh Kompetensi Dan Independensi Auditor Terhadap Kualitas Audit Pada Kap Di Wilayah Malang Raya - Gunur, Alfonsa Meltisiana; Sulistyo, Sulistyo; Setiyowati, Supami Wahyu (Jurnal Riset Mahasiswa Akuntansi, 2018)
The development of an increasingly advanced era of globalization leads to intense competition in the business world. This is seen in the business world to always maintain the accuracy and accountability of financial statements through auditing activities. In auditing financial statements required a competent and independent auditors in order to produce audit quality. However, there are still many cases that hit public accountants so that the public doubts the competence and independence of auditors. This research was conducted by distributing questionnaires to auditors in KAP Malang Raya area. The method used is multiple linear regression analysis. Based on the research, the competence and the independence value of sig 0,037 are smaller than 0,05,the competence value of sig 0,019 is smaller than 0,05, independence of sig value. 0.009 is smaller than 0,05 From the results of this study, 1) competence and independence has simultaneously effect on audit quality, 2) Competence has partial effect on audit quality and 3) Independence has partial effect affect on audit quality.